E-mpowering Learning: Innovating Entrepreneurship Education through Digital Media Inclusion and Digipreneur Approach at Andikpas LPKA Class I Palembang - Ajismanto, Fahmi; Martini, Rita; Sayuti, A. Jalaludin; Simanjuntak, Tiur; Febrianty, Febrianty; Barovih , Guntoro (Information Technology and Science (ITScience), 2024)
This study aims to develop E-Mpowerment learning media that involves the inclusion of Digipreneur entrepreneurship at Andikpas LPKA Class I Palembang. The development method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study involves education experts, entrepreneurship experts, and students of Andikpas LPKA Class I Palembang as respondents. The result of the development of E-Mpowerment learning media is an interactive digital platform that provides entrepreneurship learning materials tailored to the needs of students at Andikpas LPKA Class I Palembang. The platform is equipped with interactive learning features such as instructional videos, business simulations, and interactive quizzes. Additionally, the platform provides content that can be accessed independently by students and supports Digipreneur entrepreneurship inclusion. This study has generated positive feedback from education experts, entrepreneurship experts, and students. They stated that the E-Mpowerment learning media is effective in improving students' understanding of entrepreneurship concepts, digital skills, and learning motivation. Furthermore, Digipreneur entrepreneurship inclusion provides opportunities for students to develop creativity, innovation, and an entrepreneurial mindset. In conclusion, this study has successfully developed effective E-Mpowerment learning media to enhance entrepreneurship skills among students at Andikpas LPKA Class I Palembang. This learning media provides an interactive and inclusive learning experience through the Digipreneur entrepreneurship approach. It is hoped that this research can serve as a reference for the development of innovative and technology-relevant learning media in the context of entrepreneurship education.